Data Protection Requirement for a Successful European Citizen’s Initiative - Yocheva, Katerina (Yearbook of the Law Department, 2020)
Under consideration in the present article is the legal regulation of the data protection requirement with regard to European citizen’s initiatives (ECI). The legal regulation aims to guarantee that when organising and monitoring an ECI all the involved parties – organisers, Member States and the European commission–guarantee full data protection of the supporters to the given ECI. Regarding the review of Regulation (EU) 211/2011 there is reference to a technical study made in 2017, entitled Study on data requirements for the European Citizens’ Initiative. It was made with regard to one of the major issues of ECI that concerns the level and the variety of data provision in support of a given ECI.